Obstructive Sleep Apnea pada Usia Muda - Maulida, Adinda Ilsa (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Obstructive Sleep Apnea (OSA) is a respiratory disorder during sleep characterized by periodic narrowing and obstruction of the pharyngeal airway. OSA patients experience many symptoms that involve a series of physiological processes that lead to various diseases. A number of studies have explained that OSA does not only occur in middle-aged adults but can also occur at a young-aged adults. OSA especially at a young-aged adults remains a challenge because this sleep disorder is mild or even asymptomatic at a young-aged adults and the gold standard examination that is polysomnography, is expensive and time consuming to do. This literature review discusses the incidence of OSA at a young age, especially regarding its impact on students' health, academic achievement and economics